2022
DOI: 10.3390/cells11233874
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Lung Vacancy Mouse Model through CRISPR/Cas9-Mediated Deletion of Thyroid Transcription Factor 1 Exon 2

Abstract: A developmental niche vacancy in host embryos is necessary for stem cell complementation-based organ regeneration (SCOG). Thyroid transcription factor 1 (TTF-1) is a tissue-specific transcription factor that regulates the embryonic development and differentiation of the thyroid and, more importantly, lungs; thus, it has been considered as a master gene to knockout in order to develop a lung vacancy host. TTF-1 knockout mice were originally produced by inserting a stop codon in Exon 3 of the gene (E3stop) throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Georg et al [17] described the first case of malignant mesothelioma with thyroid posure in the cytocentrifuged preparations. Conversely, the high specificity of TTF-1 in pulmonary adenocarcinoma in our study was comparable to that reported by others, suggesting that TTF-1 should be used as an essential immunocytochemical marker in body cavity fluid cytology [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Georg et al [17] described the first case of malignant mesothelioma with thyroid posure in the cytocentrifuged preparations. Conversely, the high specificity of TTF-1 in pulmonary adenocarcinoma in our study was comparable to that reported by others, suggesting that TTF-1 should be used as an essential immunocytochemical marker in body cavity fluid cytology [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 88%
“…Although TTF-1 had high sensitivity and specificity in this study and other studies [4][5][6][7][8][9][10][11][12][13][14][15], the definitive diagnosis of primary carcinoma sites in effusions requires a panel of immunohistochemical markers. Takano et al [10] discovered that a panel of markers, including GATA-3, PAX-8, and TTF-1, helped identify or exclude common primary sites of carcinoma in effusions with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation